Application of Civil Servant Discipline at Batam City Education Office in Socio-Psycho-Juridical Perspective - Jelita Adelina Bago; Rina Shahriyani Shahrullah; Nurlaily Nurlaily (Jurnal Indonesia Sosial Teknologi, 2024)
The Indonesian state has Civil Servants who have functions as public servants, glue and unify the nation as well as policy implementers as state civil servants. But there are also employees from government agencies who are lazy at work and arrive late, this is an act that is not only detrimental to yourself, but can also harm others and the organization where you work. Violations of work discipline often create discomfort in the work environment, interfere with productivity, and damage relationships between colleagues. For example, what happened in Batam City was that two civil servants who skipped work were dismissed for violating the code of ethics. Therefore, this study aims to analyze and provide recommendations for efforts to improve the application of civil servant discipline, especially at the Batam City Education Office. This research was obtained through in-depth interviews with the Head of the Batam City Education Office and civil servant staff as well as analyzing with documents related to civil servant discipline regulations, journals, research results and books. Based on the results of the study, the application of civil servant discipline at the Batam City Education Office is still not optimal. Things that have not been optimal in the social field related to human relations on the productivity of civil servants, the psychological field is the awareness and willingness of individuals to contribute positively in their work environment, while the related juridical field has not been optimal in implementing legal certainty in implementing civil servant discipline due to the lack of firmness from the Head of the Batam City Education Office in cracking down on civil servants who are not disciplined at work. Thus, it is recommended to consider these socio-psycho-juridical factors, so that the application of civil servant discipline at the Batam City Education Office can be carried out effectively and efficiently, and can improve the performance and productivity of civil servants within the Batam City Education Office.